Islamic Legal Review on Granting a Surname to an Illegitimate Child (Case Study in Pangururan Village, Sumbul District) - Jateng GP. Siburian; Ilhamsyah Pasaribu (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to examine the Islamic legal perspective on the practice of granting clan names to children born out of wedlock in Pangururan Village, Sumbul District. This phenomenon is noteworthy because the granting of a clan name is part of the Batak Toba tradition, which holds social, kinship, and identity values, while in Islamic law, the lineage of a child born out of wedlock is subject to specific regulations. The study employs a qualitative method with a case study approach, using in-depth interviews, observation, and document analysis. The findings reveal that the granting of a clan name to children born out of wedlock in Pangururan Village is carried out to preserve family dignity, strengthen social relations, and prevent discrimination against the child. However, from an Islamic legal perspective, the lineage of a child born out of wedlock can only be attributed to the mother and her family, not to the biological father or his family. Therefore, granting a clan name that implies lineage to the biological father is not in accordance with the principles of lineage in Islamic law. The study recommends dialogue between traditional leaders and local scholars to find solutions that respect cultural values while adhering to the provisions of Islamic law.